Long-Term Effects of Left Ventricular Assist Device Therapy on Pulmonary Vascular Resistance in Patients Bridged to Heart Transplant. Issue 3 (15th August 2019) - Han, Jason J; Zaheer, Salman; Kanade, Rahul; Chung, Jennifer; Chen, Carol W; Gaffey, Ann C; Justice, Christyna; Ameer, Alyse E; Rame, J Eduardo; Acker, Michael A; Atluri, Pavan
No abstract available